Experimental Investigation of Reactive Powder Concrete exposed to Elevated Temperatures. (20th November 2020) - P.R., Kannan Rajkumar; Mathangi, Durga Prasad; C, Sudha; M, Neelamegam
Graphical abstract: Highlights: The mechanical and durability properties of the RPC with micro steel fibres is experimentally studied. The strength of RPC in compression and flexure with fibres reached 130 MPa and 44.21 MPa through optimized parameters. The use of micro steel fibres is vital in RPC to improve the strength in compression, flexure and energy absorption capacity. Exposing the specimens to Sulphuric attack compressive strength also decreased 49.58%, 54.32%, 64.19% at 10, 20, 30 days. The procedure proposed of preparing RPCs can be used in practical projects. Abstract: The development of new generation concrete by eliminating the coarser particles such as coarse aggregate and utilization of micro-particles like silica fume, quartz powder and sand thereby introducing reactive powder concrete (RPC) is presented in the present work. This study investigates mechanical properties of specimens with the addition of the RPC with micro-fiber reinforcement, thereby investigating the compressive strength, modulus of elasticity, flexural strength, ductility, and energy absorption under different curing conditions. By adding micro-particles in concrete, a compressive strength of 120 MPa and a flexural strength of 44.21 MPa is achieved with different stages of curing by adding 2% of fibers at 28 days. The study is also extended to know the durability aspects by subjecting the specimens to acid attack.